Facile hydrothermal synthesis and optical properties of monoclinic CePO 4 nanowires with high aspect ratio - Nuengruethai Ekthammathat (2018)
One-dimensional cerium phosphate (CePO4) nanowires (NWs) were successfully synthesized by a facile and simple hydrothermal method at 200°C for 12 h, using Ce(NO3)3·6H2O and Na3PO4·12H2O as starting materials, and followed by pH adjusting to be 13 using HNO3(conc.). Phase, morphologies, and vibration modes of the as-synthesized CePO4products, characterized by XRD, SEM, TEM, and FTIR, were proved to be perfect and uniform monoclinic CePO4nanowires with aspect ratio of more than 250 for the product synthesized in the solution with the pH of 1. The UV-visible and photoluminescence (PL) spectrometers were used to investigate optical properties of the as-synthesized monoclinic CePO4nanowires. © 2012 Nuengruethai Ekthammathat et al.